2001
DOI: 10.1159/000050766
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Neurovascular Compression of the Left Lateral Medulla oblongata in Ischemic Stroke

Abstract: Hypertension is a major risk factor for stroke. Neurovascular compression (NC) of the left ventrolateral medulla oblongata may cause arterial hypertension. We evaluated the relationship between the two ischemic stroke patients. We classified 69 patients under 50 years old (49 men and 20 women, aged 43.6 ± 7.3 years) based on magnetic resonance imaging findings as follows: NC patients (n = 38; 10 with NC on the right side, 18 with NC on the left side, and 10 with NC on both sides) and non-NC patients (n = 31). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In some specific cases, infarction involving the lateral medulla (Wallenburg syndrome), leads to hypertension and it can be shown that this region of brain is important in blood pressure control. 1,2 Similarly infarction of the insula may result in varying degrees of autonomic dysfunction, including acute hypertension. Acute hypertension may also been seen as a terminal event among patients with massive edema and rostral-caudal herniation, either due to malignant middle cerebral artery or cerebellar infarction; however, this occurs usually in the 24-96hour timeframe after stroke onset.…”
Section: Michael D Hill University Of Calgary Calgary Alberta Canadamentioning
confidence: 99%
“…In some specific cases, infarction involving the lateral medulla (Wallenburg syndrome), leads to hypertension and it can be shown that this region of brain is important in blood pressure control. 1,2 Similarly infarction of the insula may result in varying degrees of autonomic dysfunction, including acute hypertension. Acute hypertension may also been seen as a terminal event among patients with massive edema and rostral-caudal herniation, either due to malignant middle cerebral artery or cerebellar infarction; however, this occurs usually in the 24-96hour timeframe after stroke onset.…”
Section: Michael D Hill University Of Calgary Calgary Alberta Canadamentioning
confidence: 99%